Structural architecture and displacement accomodation mechanisms at the termination of the Priestley Fault, northern Victoria Land, Antarctica - F, Storti; ROSSETTI, FEDERICO; SALVINI, Francesco (Tectonophysics, 2001)
We present the results of field investigations carried out at the southern termination of the Priestley Fault, a major Cenozoic right-lateral strike-slip fault system in northern Victoria Land, Antarctica. The Priestley Fault was originally traced from offshore seismic profiles. Its onshore prosecution was inferred from the regional geological picture. Our work provides the first robust dataset on the kinematics and structural architecture of the Priestley Fault. The fault system includes a principal displacement zone (PDZ), where most horizontal displacement is accounted for, and a transtensional splay zone (TSZ) in the southern side consisting of a major basin at the fault tip, the Terror Rift, and minor ones paralleling it cratonward. Part of the strike-slip displacement is transferred by fault splaying from the principal displacement zone to the basin-boundary faults in the transtensional splay zone. The principal displacement zone is characterised by strongly transpressive deformation and this contrasts with the extensional component occurring in the transtensional splay zone. Such a contrast is only apparent because the two regions are kinematically linked. Transfer of the residual right-lateral strike-slip displacement from the tip region of the principal displacement zone to the basin-boundary fault systems of the Terror Rift represents the most effective displacement compensation mechanism at the termination of the Priestley Fault. It provides an additional solution for reducing the well known and still fully unsolved discrepancy between large translations of adjacent crustal blocks and the lack of comparable displacement values in their boundary strike-slip fault systems. The unquestionable evidence of intense Cenozoic brittle deformations in north Victoria Land imposes a re-examination of the regional tectonic framework, commonly interpreted as the mere result of the Early Paleozoic Ross Orogeny.